Spatialization of the urban knowledge related to the commercial real estate of waqfs - Çöteli, Methiye Gül (Turkish Historical Society e-magaza@ttk.org.tr, 2018)
The major aim of this research is to examine the impact of waqfs on built urban environment in terms of formation and development, and to spatialize the urban knowledge obtained from the waqfiyas. In particular, the study will trace the influence of waqfs on the creation and sprawl of the historical commercial zone of Kayseri, in Turkey. The research is based on waqfiyas and maps during the Ottoman period. The resulting maps and tables highlight commercial real estate of waqfs in the city. The findings of the study indicate that waqfiyas which can be used as a navigational tool are the subjective cartography of the built environment both in urban and rural areas. © 2018 Turkish Historical Society. All rights reserved.
Vakfiyelere göre ticaret yapilarina dair kentsel bilginin mekana indirgenmesi
Keywords: Bazaar; Built urban environment; Historical commercial zone; Navigation; Spatial distribution; Urban knowledge; Urban space; Waqf institution